Penerapan Website Sebagai Sarana Promosi Wisata Budaya pada Kabupaten Lombok Timur - Sudianto, Aris (Fakultas Teknik Universitas Hamzanwadi, 2018)
Web-based cultural tourism information system is used as a tool in delivering information on tourism and culture in East Lombok to people who want to know the tourist areas in East Lombok. The system, web-based tourist information system is one form of media or means. Promotion of cultural tourism in East Lombok Regency which aims to attract both local and foreign tourists to visit Lombok Island, especially East Lombok. This research is expected to be useful as a medium of information and promotion of tourism potential in East Lombok, so that the community will be more familiar with the tourism places of the area visited, besides that the location of tourists by tourists can impact on the economic aspects of the surrounding communities. . Research methods conducted by researchers include observation, interviews with related parties, and literature studies related to the issues raised. In designing this information system, researchers use several programming languages and databases, including PHP and Mysql. With this information system, it is expected that tourism in East Lombok will increase.DOI : 10.29408/jit.v1i1.878